Frederick Schwatka (1849-1892) - Davis, Richard C. (ARCTIC, 1984)
. in spite of having gained recognition as a certified barrister, a trained medical doctor, and fighting cavalry officer, Frederick Schwatka will best be remembered as a superlative arctic traveller who brought the 30-year-long search for the missing Franklin expedition to a close. He not only made the longest sled journey on record at the time, but in gathering his nearly conclusive evidence that none of Franklin's official or scientific papers had survived, Schwatka made clear that white men could travel extensively in the Arctic without serious injury or illness if they adopted native methods, a "discovery" often attributed to Vilhjalmur Stefansson some three decades later. . Schwatka's arctic interests were sparked in the 1860s, when neswpapers reported C.F. Hall's searches for Franklin's missing ships and crew. . A search, sponsored by the American Geographical Society and financed by private backers, began to take shape, and Schwatka volunteered to lead it. . Schwatka did find numerous relics of the missing expedition, including part of one of the ship's boats, a miscellaneous collection of buttons and remnants of cloth, and several graves and corpses. He gave decent burial to all mortal remains and positively identified the grave of Lt. John Irving, third officer of the Terror. As well, he made a number of minor geographical discoveries, . Yet the genuine significance of "Schwatka's search" - as this exhaustive investigation of the region came to be popularly termed - is that it laid to rest any hope that the records of the Franklin party would ever be retrieved. Schwatka's incredible year-long sled journey opened new possibilities in arctic travel if scientific and exploratory parties would adopt native methods. .